An efficient deep learning approach to detect skin Cancer - Islam, Ashfaqul; Khan, Daiyan; Chowdhury, Rakeen Ashraf (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.